Enhancing the GROW syntax in GAARANTUNG: a study on the coaching model development in education - Sadewo, Yosua Damas; Wibawa, Basuki; Hanafi, Ivan; Purnasari, Pebria Dheni; Saputro, Totok Victor Didik (Intelektual Pustaka Media Utama, 2025)
The selection process of a coaching model should be an initial consideration before conducting training activities. However, the limited availability of coaching models hinders the delivery of quality training programs. Therefore, it is necessary to have options for coaching models. This research aims to develop a goal, actual, alternative, plan, action, monitoring, and reflection based on blended learning (GAARANTUNG) a coaching model rooted in goal, reality, option, will (GROW) with the addition of action, monitoring, and reflection elements based on blended learning. The development of this coaching model is conducted by adopting the analysis, design, development, implementation, and evaluation (ADDIE) research and development concept, which involves three main steps: analysis, design, and development. The results of this research include the availability of a coaching model that meets the needs, including the incorporation of technological elements within GAARANTUNG. The GAARANTUNG coaching model is the improved version of the GROW coaching model, which only focuses on action planning, and the goal, reality, option, will-monitoring, evaluation (GROW-ME) coaching model, which lacks a description of coaching during action and does not include digital technology elements. The refinement of the syntax in GROW and GROW-ME to form GAARANTUNG is a crucial step in providing a coaching model that aligns with the needs and facilitates the implementation of training programs, specifically targeting the main needs of participants, including teachers and school principals.